ANALISIS KARAKTERISASI SERBUK BIOKERAMIK DARI CANGKANG TELUR AYAM BROILER - Hendri Van Hoten (ROTOR, 2020)
The research is about analysis of Nano Sized Bioceramic Characterization Using Particle Size Analyzer (PSA). In the previous research, optimization of the parameters of making nano powders on Ball Mill machines using the Taguchi and ANOVA methods. The optimum parameters of the Taguchi Design analysis were grinding rate, grinding time and Ball Powder Ratio respectively 250 rpm, 3 hours and 1: 6. After that the characterization of the powder use a Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM). Powder size measurement use SEM tools obtained the smallest average size of 1.305 mm while using TEM tools showed the average size of the smallest powder between 50-100 nm. TEM test results were confirmed again using PSA. The results of the characterization using PSA showed that the particle size in the range 100-300 nm was approximately 80%